COLA-GLM: collaborative one-shot and lossless algorithms of generalized linear models for decentralized observational healthcare data - Wu, Qiong; Reps, Jenna M.; Li, Lu; Zhang, Bingyu; Lu, Yiwen; Tong, Jiayi; Zhang, Dazheng; Lumley, Thomas; Brand, Milou T.; Van Zandt, Mui; Falconer, Thomas; He, Xing; et al. (NPJ digital medicine, 2025)
Clinical insights from real-world data often require aggregating information from institutions to ensure sufficient sample sizes and generalizability. However, patient privacy concerns only limit the sharing of patient-level data, and traditional federated learning algorithms, relying on extensive back-and-forth communications, can be inefficient to implement. We introduce the Collaborative One-shot Lossless Algorithm for Generalized Linear Models (COLA-GLM), a novel federated learning algorithm that supports diverse outcome types via generalized linear models and achieves results identical to a pooled patient-level data analysis ( lossless) with only a single round of aggregated data exchange ( one-shot ). To further protect aggregated institutional data, we developed a secure extension, secure-COLA-GLM, utilizing homomorphic encryption. We demonstrated the effectiveness and lossless property of COLA-GLM through applications to an international influenza cohort and a decentralized U.S. COVID-19 mortality study. COLA-GLM and secure-COLA-GLM offer a scalable, efficient solution for decentralized collaborative learning involving multiple data partners and diverse security requirements.